2007
DOI: 10.1016/j.jmaa.2006.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic blow-up behavior for a nonlocal degenerate parabolic equation

Abstract: In this paper, we investigate the positive solution of nonlinear degenerate equation u t = f (u)( u + a(x) Ω u dx) with Dirichlet boundary condition. The blow-up criteria is obtained. Furthermore, we prove that under certain conditions, the solutions have global blow-up. When f (u) = u p , 0 < p 1, we gained blow-up rate estimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…It also arises in the study of the flow of a fluid through a homogeneous isotropic rigid porous medium with internal localized source, see [3,[6][7][8]. The studies on the blow-up and global existence of solutions for the equations or systems not in divergence form with local, nonlocal or localized terms can be found in [2,4,5,[9][10][11][12][16][17][18][19][20][21].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also arises in the study of the flow of a fluid through a homogeneous isotropic rigid porous medium with internal localized source, see [3,[6][7][8]. The studies on the blow-up and global existence of solutions for the equations or systems not in divergence form with local, nonlocal or localized terms can be found in [2,4,5,[9][10][11][12][16][17][18][19][20][21].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…have been studied in [4] and [9]. When a is a positive constant, Deng et al in [9] proved that the solution blows up in finite time if and only if ∞ δ ds sf (s) < ∞ and a > 1/μ, where δ > 0 is a constant and μ is defined as…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…It was shown that the blow-up occurs for large initial data if q > p > 1, while all solutions exist globally if 1 ≤ q < p. As for the critical case p = q, they proved that whether or not the solutions blow up in finite time depending on the comparison of |Ω| and k. Global blow-up property was also proved. For more works on parabolic equations or systems with localized or nonlocal sources, we refer the readers to [1,6,18,25,29]. On the other hand, parabolic equations with nonlocal boundary conditions also arise naturally in applied sciences (see [4,9,10]).…”
Section: Introductionmentioning
confidence: 99%
“…Such a problem can describe a variety of physical phenomena which arise, for example, in the study of the flow of a fluid through a homogeneous isotropic rigid porous medium or in the studies of population dynamics (see [1], [3], [5], [6], [7] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…with the homogeneous Dirichlet boundary condition and positive initial data, has been studied in [3], [4], where p > 0. It was proved that the solution blows up in finite time if and only if µ > 1/a, where µ is defined in (1.4) below.…”
Section: Introductionmentioning
confidence: 99%